Double Coronary–Cameral Fistula: Right Coronary Artery and Circumflex to Left Atrium - Mauricio Farias Hernandez; Roberto Hipólito Hernandez; Grecia Rosangela Perez Siller (Annals of Internal Medicine: Clinical Cases)
Coronary fistulas are an abnormal communication of the coronary arteries with the cardiac chambers or any vascular structure. Most are detected incidentally. Transthoracic echocardiogram is essential for evaluation, coronary computed tomography angiography can be useful in planning the procedure, allowing excellent anatomical delineation, and cardiac magnetic resonance imaging can help to outline the anatomy; however, the gold standard is coronary angiography. Treatment can be pharmacologic, surgical, or transcatheter. We present the case of a 71-year-old woman with angina and dyspnea in whom the diagnostic approach demonstrated the presence of coronary–cameral fistulas for which pharmacologic management was decided.